Technical guidance on making fish shredded meat for coastal communities in Kendari City - Hafid, Harapin; Umasugi, Mohbir; Dedu, La Ode Arfan; Aslan, La Ode M.; Ananda, Siti Hadrayanti (Talenta Publisher Universitas Sumatera Utara, 2025)
This community service activity aimed to provide knowledge and skills to women in coastal villages on how to make fish floss from tuna scraps, resulting in floss with a texture, aroma, and taste similar to beef floss. The activity was conducted in Abeli Subdistrict, with participants from five coastal neighborhoods in Kendari City: Abeli Village (3 participants), Lapulu Village (3 participants), Talia Village (5 participants), Nambo Village (4 participants), and Sambuli Village (4 participants), totaling 19 participants. The activity was conducted using educational sessions and demonstrations. The evaluation results showed that the community, particularly the women who participated in the training, were able to master and apply the fish floss production techniques taught. Based on observations by the program implementers, approximately 90% of the women were already able to make fish floss, as most participants had previously been accustomed to making traditional Bajabu fish floss. With this knowledge, they were able to utilize their free time productively by producing fish floss from tuna scraps.